Straightening Some "tangles" in the Tale of Traité - Ricketts, Mac Linscott (Archaeus, 2002)
Central and Eastern European Online Library - CEE journals, documents, articles, periodicals, books available online for download, Zeitschrfitendatenbank, Online Zeitschriften, Online Zeitschriftendatenbank